2014
DOI: 10.13087/kosert.2014.17.1.091
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Habitat-using of Siberian Roe Deer in Seoraksan(Mt.) National Park

Abstract: This study was conducted to obtain the basic research about Siberian roe deer (Capreolus pygargus), and to establish a conservation area into Seoraksan(Mt.) National Park, South Korea.We recorded Siberian roe deer field signs (bedding sites, feeding areas, feces and tracks etc), and habitat variables such as nearest distance to the watercourse, trails, slope, aspect, forest type and 2 (32% of the total area) followed by 244.3km 2 buffer area (62.2% of the total area), and 22.9km 2 unsuitable habitat area (5.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…While preferences for slope gradients may differ for each wildlife species, a common preference for gentle slopes can be observed in many mammalian species in Korea [ 42 ], including Siberian roe deer ( Capreolus pygargus ) [ 43 ], leopard cat [ 17 ], Korean water deer [ 15 , 44 ], and wild boar ( Sus scrofa ) [ 45 ]. Compared to other neighboring provinces, the adequate forests with gentle slope gradients found within the study region can serve as ecological corridors, facilitating movement [ 44 ], enhancing the availability of water [ 43 ] and food resources [ 44 ], providing sites for resting and hunting [ 46 ], and for avoiding mountainous carnivores [ 15 ] and human conflicts [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…While preferences for slope gradients may differ for each wildlife species, a common preference for gentle slopes can be observed in many mammalian species in Korea [ 42 ], including Siberian roe deer ( Capreolus pygargus ) [ 43 ], leopard cat [ 17 ], Korean water deer [ 15 , 44 ], and wild boar ( Sus scrofa ) [ 45 ]. Compared to other neighboring provinces, the adequate forests with gentle slope gradients found within the study region can serve as ecological corridors, facilitating movement [ 44 ], enhancing the availability of water [ 43 ] and food resources [ 44 ], providing sites for resting and hunting [ 46 ], and for avoiding mountainous carnivores [ 15 ] and human conflicts [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roe deer's altitudinal preferences reportedly differ with habitat conditions (Mysterud 1999, Qin 2011, Park and Lee 2014). In this study, roe deer tended to occupy high‐altitude areas above 800–1000 m a.s.l.. Altitude can affect roe deer's ecology in several ways, including changes in microclimate (Mysterud et al 1997, Pagon et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The wildlife generally consider the gradient of slope as an essential factor for hiding or rearing their infants upon selecting their habitat, and the preferred slope gradients are varied with species (Congalton et al 1993). The roe deer was found to inhabit areas with slope gradients of 20-30 (Park and Lee 2014), and the other study reported that ecological corridor for the movement of roe deer is most appropriate to build with slope gradients of 24-32 (Jeong 2011). In the case of boars' habitat, there is a preference to inhabit areas with a relatively gentle slope (less than 20 ) (Keimyung University 2015).…”
Section: Slope Gradientsmentioning
confidence: 99%
“…Generally, there is higher moisture content and soil fertility on the north and east slope compared to the others. Due to these certain condition in the north and east slope, lots of invasion and vigorous growth of the vegetation have encouraged the wildlife movement and hiding (Chen et al 1999, Park andLee 2014).…”
Section: Aspectmentioning
confidence: 99%